The Keefektifan Panduan Guru Dengan Pendekatan Contextual Problem dalam Pembelajaran Tematik - Irfan Wahyu Prananto (Jurnal Inovasi Pendidikan Dasar, 2019)
The study aims to determine the effectiveness of teacher guides with contextual problem approaches in thematic learning. This research is a follow-up study of teacher guide products developed, used in thematic learning on the themes of various jobs, sub-themes of types of work with a contextual problem approach which through the process of observing, asking, trying, reasoning, and communicating. The five processes are deemed necessary, because according to the philosophy of thematic learning namely meaningfulness in the learning process. Students are able to construct their own meanings, from contextual learning prepared by the teacher. In this study, the true quantitative experimental method was used in the type of posttest-only control group design. Where the main characteristic of this study is the placement of subjects in groups randomly, provided the subject characteristics are considered the same. The indicators of success used are, effective if the classical completeness of the experimental class exceeds 80%. The conclusion of this study is the teacher's guide to the contextual problem approach in effective thematic learning, with 84% classical completeness and more than 65% student activity.